Pengaruh Kompensasi Non Finansial Dan Reduction Job Stres Terhadap Kinerja Karyawan - Devi Kurnia Mandansari; Honorata Ratnawati Dwi Putranti (Journal Of Business, Finance, and Economics (JBFE), 2024)
This research aims to empirically test the effect of non-financial compensation and job stress reduction on employee performance. Non-financial compensation and reducing job stress have an important role in improving employee performance. This type of research uses quantitative research by distributing questionnaires to respondents. The population of this research is employees at manufacturing company "X" totaling 130 employees. The sample size used was 82 samples with a random sampling technique. The data analysis technique uses multiple linear regression analysis with SPSS 23. The research results show that non-financial compensation has a positive and significant effect on employee performance. This can be seen from the calculated t value which is greater than the t table and significantly smaller than 0.05. Reducing job stress has a positive and significant effect on employee performance. This can be seen from the calculated t value which is greater than the t table and the significance level is smaller than 0.05. These results show that financial compensation and job stress reduction are needed to improve employee performance at company "X"